Feasibility Study on The Construction of A Public Vocational High School in Batam City - Syamsurijal, Syamsurijal (Devotion : Journal of Research and Community Service, 2026)
This study aims to examine the feasibility of the development of State Vocational High Schools (SMK) in Batam City through a multi-aspect analysis approach that includes market and demand aspects, social impact, linkage with the Business and Industrial World (DUDI), and legality aspects. The methodology used was a descriptive-evaluative quantitative approach with primary data collection through a structured questionnaire involving three groups of respondents: (1) parents/guardians of junior high school students in Bengkong District (96 respondents) and Batu Aji District (96 respondents), (2) the community around the location (105 respondents in Bengkong and 96 respondents in Batu Aji), and (3) DUDI partners as many as 76 companies. The final eligibility decision was determined using a Weighted Scoring Model with weights: Market Aspects (30%), DUDI (30%), Social (20%), and Legal (20%). The results of the study showed that the Bengkong area received a composite score of 4.11 (Feasible category) and the Batu Aji area received a score of 4.22 (Very Feasible category).The DUDI survey revealed the actual recruitment needs of 4,998 vocational school graduates per year with a projection of 12,517 people in the next 3-5 years. Priority areas of expertise include Mechanical Engineering (3.91), Electronics Engineering (3.78), Accounting (3.71), Electrical Engineering (3.68), and TKJ (3.64). Community support reached 93.33% in Bengkong and 92.7% in Batu Aji. The research concludes that the construction of SMKN in Batam City is FEASIBLE and recommends that preparations be made immediately for the establishment with a skill program tailored to the industrial characteristics of each region.